Disability in activities of daily living and severity of dyskinesias determine the handicap of Parkinson´s disease patients in advanced stage selected to dbs - Coelho, Miguel (2019)
"BACKGROUND: There is scarce data on the level of handicap in Parkinson's disease (PD) and none in advanced stage PD. OBJECTIVE: To assess the handicap in advanced stage PD patients with disabling levodopa-induced motor complications selected to deep brain stimulation (DBS). METHODS: Data was prospectively recorded during routine evaluation for DBS. Handicap was measured using London Handicap Scale (LHS) (0 = maximal handicap; 1 = no handicap). Disease severity was evaluated using the Hoehn & Yahr scale and the UPDRS/MDS-UPDRS, during off and on after a supra-maximal dose of levodopa. Schwab and England Scale (S&E) was scored in off and on. Dyskinesias were scored using the modified Abnormal Involuntary Movement Scale (mAIMS). Results concern cross-sectional assessment before DBS. RESULTS: 100 PD patients (mean age 61 (±7.6); mean disease duration 12.20 (±4.6) years) were included. Median score of motor MDS-UPDRS was 54 in off and 25 in on. Mean total LHS score was 0.56 (±0.14). Patients were handicapped in several domains with a wide range of severity. Physical Independence and Social Integration were the most affected domains. Determinants of total LHS score were MDS-UPDRS part II off (β= -0.271; p = 0.020), S&E on (β= 0.264; p = 0.005) and off (β= 0.226; p = 0.020), and mAIMS on (β= -0.183; p = 0.042) scores (R2  = 29.6%). CONCLUSIONS: We were able to use handicap to measure overall health condition in advanced stage PD. Patients were moderately to highly handicapped and this was strongly determined by disability in ADL and dyskinesias. Change in handicap may be a good patient-centred outcome to assess efficiency of DBS."